Fire sales by euro area banks and funds: What is their asset price impact? - Harun Mirza; Diego Moccero; Spyros Palligkinis; Cosimo Pancaro (European Central Bank (ECB), 2020)
The assets under management of investment funds have soared in recent years, triggering a debate on their possible implications for financial stability. We contribute to this debate assessing the asset price impact of fire sales in a novel partial equilibrium model of euro area funds and banks calibrated over the period between 2008 and 2017. An initial shock to yields causes funds to sell assets to address investor redemptions, while both banks and funds sell assets to keep their leverage constant. These fire sales generate second-round price effects. We find that the potential losses due to the price impact of fire sales have decreased over time for the system. The contribution of funds to this impact is lower than that of banks. However, funds' relative contribution has risen due to their increased assets under management and banks' lower leverage and rebalancing towards loans. Should this trend continue, funds will become an increasingly important source of systemic risk.
Keywords: G1; G21; G23; 330; Investment funds; banks; fire sales; second-round price effects; financial contagion; financial stability